A Proposal for a Standardized Imaging Algorithm to Improve the Accuracy and Reliability for the Diagnosis of Thoracolumbar Posterior Ligamentous Complex Injury in Computed Tomography and Magnetic Resonance Imaging. Issue 3 (April 2023) - Aly, Mohamed M.; Al-Shoaibi, Abdulbaset M.; Aljuzair, Ali H.; Issa, Tariq Ziad; Vaccaro, Alexander R.
Study Design: Systematic Literature Review. Objective: To propose a systematic imaging algorithm for diagnosing posterior ligamentous complex (PLC) injury in computed tomography (CT) and magnetic resonance imaging (MRI) to improve the reliability of PLC assessment. Methods: A systematic review was conducted following PRISMA guidelines. The Scopus database was searched from its inception until July 21, 2022, for studies evaluating CT or MRI assessment of the PLC injury following thoracolumbar trauma. The studies extracted key findings, objectives, injury definitions, and radiographic modalities. Results: Twenty-three studies were included in this systematic review, encompassing 2021 patients. Five studies evaluated the accuracy of MRI in detecting thoracolumbar PLC injury using intraoperative findings as a reference. These studies indicate that black stripe discontinuity due to supraspinous or ligamentum flavum rupture is a more specific criterion of PLC injury than high-signal intensity. Thirteen papers evaluated the accuracy or reliability of CT in detecting thoracolumbar PLC injury using MRI or intraoperative findings as a reference. The overall accuracy rate of CT in detecting PLC injury was 68-90%. Two studies evaluate the accuracy of combined CT findings, showing that ≥2 CT findings are associated with a positive predictive value of 88-91 %. Vertebral translation, facet joint malalignment, spinous process fracture, horizontal laminar fracture, and interspinous widening were independent predictors of PLC injury. Conclusion: We provided a comprehensive imaging algorithm for diagnosing PLC in CT and MRI based on available literature and our experience. The algorithm will potentially improve the accuracy and reliability of PLC assessment, however it needs multicentre prospective validation.